Youtuber's Strategy in Determining Opinion Leaders on Covid-19 Pandemic Video Content - Hayana, Hayana; Ramli, Ramli (IAIN Parepare, 2021)
This research is entitled Youtuber's Strategy in Determining Opinion Leader in Covid-19 Pandemic Video Content. This study at to determine: (1) What was the YouTuber video content program during the Covid-19 pandemic? (2) What was the YouTuber strategy in determining opinion leader? This research method used a descriptive qualitative approach. The data were obtained using a list of questions given to the informants. Then, the data were analyzed and reviewed. After that, an abstract was made of all the results of the interview. The number of informants was three people with different opinion leader, including whether hidden or unhidden. The selection of informants in this qualitative study used purposive sampling technique, which was a method of deliberately determining informants based on certain criteria or certain considerations. In this study, the selection of informants was based on criteria, including: number of subscribers, uploading videos during the Covid-19 pandemic, and having opinion leader. Data analysis was by using thematic data, which the findings were processed based on themes in accordance with the framework. The results of this study indicated that YouTubers had various programs such as music, vlogs, podcasts, and tutorials. This depends on the needs and passion of the YouTubers. It also showed that the YouTuber's strategy in determining opinion leader had two flow schemes. First, the YouTuber first identified the content idea to be made, then found an opinion leader by paying attention to the opinion leader criteria, such as sources of attraction and sources of trust. Second, YouTubers determined opinion leader before content was created. Information exposure obtained from opinion leader would be a reference material for the emergence of content ideas. In addition, YouTubers also paid attention to the requirements of opinion leaders such as social perception, ability in abstract thinking, emotional stability, public speaking and action.